Transforming growth factor-β in diabetic nephropathy - Karima Y. Ahmed; Walaa F. El-Bazz; Hend A. Mohamed; Maha M. Elkeshky (SpringerOpen, 2013)
Background Renal failure is a common and serious complication of long-standing diabetes mellitus. Diabetes is the most common cause of end-stage renal failure. Transforming growth factor-β (TGF-β) is one of the major growth factors involved in extracellular matrix accumulation in fibrotic disorders including diabetic nephropathy. Aim of the workThe aim of the present study was to evaluate the serum level of TGF-β as a marker for the development and progression of diabetic nephropathy. Patients and methods This work included 40 patients with diabetes and 40 healthy controls with matched age and sex. Individuals with diabetes included 25 patients with type 2 diabetes and 15 with type 1 diabetes. We considered the presence of hypertension, use of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers, and the degree of proteinuria. All patients were subjected to careful history taking, thorough physical examinations, and fundus examination. Routine laboratory tests such as analysis of complete blood count and determination of erythrocyte sedimentation rate were carried out to rule out patients with malignancy or autoimmune disease. Kidney function tests (blood urea and serum creatinine), complete urine analysis, and estimation of 24-h urinary protein or albumin, creatinine clearance, blood glucose measurement (fasting and 2 h postprandial), serum TGF-β level, and microalbuminuria were also carried out. Results The serum levels of TGF-β were statistically significantly higher in patients with diabetes compared with normal healthy people. The serum TGF-β level was statistically significantly higher in patients with diabetes with overt nephropathy compared with those without it. There was a statistically significant decrease in TGF-β levels in patients with diabetes who were taking angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers compared with those who were not taking such medications. Conclusion Serum TGF-β level increases in patients of both type 1 and type 2 diabetes and in those with diabetic nephropathy. TGF-β is considered one of the major mediators of diabetic renal fibrogenesis that Results in end-stage renal disease.